Can Naked Exclusion Be Procompetitive? - Linda Gratz; Markus Reisinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
Antitrust scholars have argued that exclusive contracts have anticompetitive, or at best neutral effects, if no efficiencies are generated. In contrast, this paper shows that exclusive contracts can have procompetitive effects, provided buyers are imperfect downstream competitors and contract breach is feasible. In that case an efficient entrant is not necessarily foreclosed through exclusive contracting but induces buyers to breach. Because breaching buyers have to pay expectation damages to the incumbent, the downstream profits they obtain when breaching must be large enough. Therefore, the entrant needs to set a lower wholesale price than absent exclusive contracting, leading to lower final consumer prices and higher welfare.
urn:nbn:de:bvb:19-epub-12733-5
Keywords: D43; K21; L12; L42; 330; Exclusive Contracting; Naked Exclusion; Contract Breach; Antitrust Policy; Vertriebsbindung; Lieferantenmanagement; Markteintritt; Wettbewerb; Theorie